Identification of DLG5 and SLC22A5 gene polymorphisms in Malaysian patients with Crohn's disease - Chua, K.H.; Lian, L.H.; Kee, B.P.; Thum, C.M.; Lee, W.S.; Hilmi, I.; Goh, K.L. (2011)
OBJECTIVE: The aim of this study was to investigate the association of DLG5 and SLC22A5 gene polymorphisms with the onset of Crohn's disease (CD) in a Malaysian cohort. METHODS: Genomic DNA of 80 CD patients and 100 healthy unrelated control individuals was extracted and analyzed via polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) on DLG5 (4136 C/A), DLG5e26 and SLC22A5 (-207 G/C) genetic polymorphisms. Data obtained from the study were then subjected to statistical analysis to test for risk association. RESULTS: Significant associations of both DLG5 polymorphisms with the development of CD in the Malaysian patients were observed in this study. The homozygous C genotype of the DLG5 polymorphism was significantly related to CD patients (P = 0.0023, OR = 2.5320), while the homozygous A was significant in control individuals (P = 0.0224, OR = 0.4480). In DLG5e26 polymorphisms, we found a significant distribution of the homozygous insA genotype in CD patients (P = 0.0006, OR = 2.8916), whereas the heterozygous insA/delA genotype was significant in controls (P = 0.0007, OR = 0.3487). We hypothesized that there might be a complex interaction of both alleles, which confered a protective effect against the onset of CD. However, we did not observe any significant correlation of SLC22A5 polymorphisms with this disease. CONCLUSIONS: In our study, both polymorphisms in the DLG5 gene were found to be associated with CD patients in Malaysia. Therefore, these loci can be potentially used as susceptibility markers in the Malaysian population.